Circulating concentrations of free thyroxine after an oral intake of liquid LT4 taken either during fasting conditions or at breakfast - Marina, Michela; Ceda, Gian Paolo; Aloe, Rosalia; Gnocchi, Cecilia; Ceresini, Graziano (Acta Biomedica Atenei Parmensis, 2017)
Background and aim of the work: Liquid levothyroxine (LT4) given at breakfast normalizes TSH in hypothyroid patients. However, a few studies are available on circulating free thyroxine (FT4) concentrations after liquid vs solid LT4 preparations. Methods: During an “ad interim” analysis on serum FT4 after 200 mcg liquid LT4 consumption while fasting in thyroidectomized thyroid cancer patients, we found that seven subjects fortuitously took liquid LT4 at breakfast. As established in the original protocol, serum FT4 was measured both at baseline as well as at 3 and 4 hours after solid or liquid LT4 consumption. We compared serum profile of FT4 in these subjects with those obtained in other subjects participating in the same study who took liquid LT4 (n. 7 subjects) or solid LT4 (n. 7 subjects) while fasting. The percentage increase of circulating FT4 was calculated at the above reported peak-times over the baseline values. Results: Circulating FT4 increased of about 40% in each group of subjects at both the 3rd and the 4th hour with no difference between these two time points in either group. The maximum FT4 % increase, irrespective of the time point, was 44.62 ± 3.05 (Mean ± SE), 44.84 ± 5.43, and 43.83 ± 1.30 after fasting solid, fasting liquid, and breakfast liquid LT4 consumption, respectively, with no differences among the three groups. Conclusions: Circulating FT4 obtained after 3 and 4 hours from the ingestion of 200 mcg liquid LT4 is not influenced by meal and is comparable with that observed after solid LT4 preparations ingested while fasting